Some issues about the application of the analytic hierarchy process to R&D project selection - Godinho, Pedro (2015)
The analytic hierarchy process (AHP) has been used in the process of selecting research and development (R&D) projects. Such a selection process usually possesses some particular features that require adjustments in the application of the AHP method, such as the existence of a large number of very different alternatives or the integration of qualitative and quantitative criteria. In this paper, we discuss the application of AHP to the selection of a portfolio of R&D projects, and we propose some methods for handling the issues that arise from such an application